DAX-Firms and Human Rights Understanding Institutional and Stakeholder Pressures along the Value Chain - Drauth, Carlo Manuel (Springer Fachmedien Wiesbaden : VS, 2018)
Carlo Manuel Drauth explores under which conditions multinational enterprises systematically manage their human rights impacts with a view to preventing corporate human rights violations across their operations. Using a multi-method research design and focusing on the 30 largest German firms, the author finds that it is neither institutional forces (e.g., standards or norms) nor stakeholder pressures (e.g., from NGOs or trade unions) alone, but their combined effect that leads to a systematic human rights management at the firm-level. This finding informs a new theoretical approach to the study of CSR, integrating institutional and stakeholder theories while taking an explicit value chain perspective. Contents Global Governance Gaps and Human Rights Abuses A Systematic Human Rights Management as a Response to Rising Societal Expectations QCA Analysis and Case Studies: Human Rights Management at the 30 DAX Firms Implications of Findings for Current Theoretical Debate and Governance Regime Target Groups Researchers and students in the fields of sustainability management, corporate social responsibility, governance, and public policy Sustainability managers, national and international policy-makers, representatives of associations, trade unions, and NGOs The Author Dr. Carlo Manuel Drauth works on governance issues, with a particular focus on corporate social responsibility (CSR). He holds a PhD from the Hertie School of Governance and has professional experience in government and business.